we can use average rate of change formula
![\frac{f(b)-f(a)}{b-a}](https://tex.z-dn.net/?f=%5Cfrac%7Bf%28b%29-f%28a%29%7D%7Bb-a%7D)
(a) x = -3 to x = -2
Firstly, we will find points
(-3, 0) and (-2,2)
now, we can plug these values into formula
and we get
![=\frac{2-0}{-2+3}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B2-0%7D%7B-2%2B3%7D)
![=2](https://tex.z-dn.net/?f=%3D2)
(b)x = -2 to x =1
Firstly, we will find points
(-2,2) and (1,-4)
now, we can plug these values into formula
and we get
![=\frac{-4-2}{1+2}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B-4-2%7D%7B1%2B2%7D)
![=-2](https://tex.z-dn.net/?f=%3D-2)
(c) x = 0 to x =1
Firstly, we will find points
(0,-3) and (1,-4)
now, we can plug these values into formula
and we get
![=\frac{-4+3}{1-0}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B-4%2B3%7D%7B1-0%7D)
![=-1](https://tex.z-dn.net/?f=%3D-1)
(d) x = 1 to x =2
Firstly, we will find points
(1,-4) and (2,0)
now, we can plug these values into formula
and we get
![=\frac{0+4}{2-1}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B0%2B4%7D%7B2-1%7D)
![=4](https://tex.z-dn.net/?f=%3D4)
(e) x = -1 to x =0
Firstly, we will find points
(-1,0) and (0,-3)
now, we can plug these values into formula
and we get
![=\frac{-3-0}{0+1}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B-3-0%7D%7B0%2B1%7D)
![=-3](https://tex.z-dn.net/?f=%3D-3)
(f) x = -1 to x =2
Firstly, we will find points
(-1,0) and (2,0)
now, we can plug these values into formula
and we get
![=\frac{0-0}{2+1}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B0-0%7D%7B2%2B1%7D)
![=0](https://tex.z-dn.net/?f=%3D0)